Modeling Sterilized Interventions and Balance Sheet Effects of Monetary Policy in a New-Keynesian Framework - Benes, Jaromir (IMF Working Papers; Working Paper ;, 2013)
We study a wide range of hybrid inflation-targeting (IT) and managed exchange rate regimes, analyzing their implications for inflation, output and the exchange rate in the presence of various domestic and external shocks. To this end, we develop an open economy new-Keynesian model featuring sterilized interventions in the foreign exchange (FX) market as an additional central bank instrument operating alongside the Taylor rule, and affecting the economy through portfolio balance sheet effects in the financial sector. We find that there can be advantages to combining IT with some degree of exchange rate management via FX interventions. Unlike "pure" IT or exchange rate management via interest rates, FX interventions can help insulate the economy against certain shocks, especially shocks to international financial conditions. However, managing the exchange rate through FX interventions may also hinder necessary exchange rate adjustments, e.g., in the presence of terms of trade shocks.